Determination of oxidant exposure during ozonation of secondary effluent to predict contaminant removal. (1st September 2016) - Zucker, Ines; Avisar, Dror; Mamane, Hadas; Jekel, Martin; Hübner, Uwe
Abstract: The use of kinetic models to predict oxidation performance in wastewater is limited due to fast ozone depletion during the first milliseconds of the reaction. This paper introduces the Quench Flow Module (QFM), a bench-scale experimental technique developed to measure the first 5–500 milliseconds of ozone depletion for accurate determination of ozone exposure in wastewater-ozonation processes. Calculated ozone exposure in QFM experiments was up to 24% lower than in standard batch experiments, strongly depending on the initial sampling point for measurement in batch experiments. However, oxidation rates of slowly- and moderately-reacting trace organic compounds (TrOCs) were accurately predicted from batch experiments based on integration of ozone depletion and removal of an ozone-resistant probe compound to calculate oxidant exposures. An alternative concept, where ozone and hydroxyl radical exposures are back-calculated from the removal of two probe compounds, was tested as well. Although the QFM was suggested to be an efficient mixing reactor, ozone exposure ranged over three orders of magnitude when different probe compounds reacting moderately with ozone were used for the calculation. These effects were beyond uncertainty ranges for apparent second order rate constants and consistently observed with different ozone-injection techniques, i.e. QFM, batch experiments, bubble columns and venturi injection. This indicates that previously suggested mixing effects are not responsible for the difference and other still unknown factors might be relevant. Results furthermore suggest that ozone exposure calculations from the relative residual concentration of a probe compound are not a promising option for evaluation of ozonation of secondary effluents. Graphical abstract: Highlights: Prediction of oxidation performance in wastewater is limited using kinetic models. Quench Flow Module was used for determination of ozone exposure via two concepts. Predicting the removal of compounds succeeded by integrating ozone depletion. Ozone exposure was inaccurately calculated from the removal of probe compound. Mass transfer or inaccuracy of rate constants limit the use of the second concept.